DYNAMICS OF PESINAUAN TRADITIONAL SCHOOL IN STRENGTHENING USING CULTURAL IDENTITY THROUGH COMMUNITY-BASED EDUCATION IN BANYUWANGI - marsiyah; I Kadek Yudiana; Mahfud (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The weakening of the younger generation's attachment to local culture due to globalization has emphasized the importance of community-based education as a strategy for strengthening cultural identity. This study analyzes the learning process, institutional roles, supporting and inhibiting factors, and the strategies of the Pesinauan Traditional School to maintain the relevance of Using culture in Banyuwangi. The method used is descriptive qualitative through in-depth interviews and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with validity testing using source triangulation. The results show that the Pesinauan Traditional School implements experiential learning through cultural practices such as dance, traditional music, Using language, weaving, and gending, which build participants' emotional attachment to local culture. Analytically, identity strengthening occurs through social engagement and community social capital, although digital media distractions are a major obstacle. Adapting the use of platforms such as TikTok and YouTube maintains cultural relevance. Different from previous studies that are generally descriptive, this study offers novelty by analyzing internal dynamics in depth. Theoretically, this article contributes to the development of experiential learning theory in the context of Traditional Schools and Gramsci's counter-hegemony against global cultural dominance.